Rozvoj miest a jeho financovanie - Žárska, Elena; Rafaj, Oliver (Univerzita Pardubice, 2017)
The importance of cities in the economic system of the country is unquestionable. They group and attract a large number of economic actors and allow them to realize intense economic interactions between them. To offer long-term benefits for inhabitants and entrepreneurs and remain attractive for them, cities need to develop continuously. Ensuring the development of the city means to create and acquire resources to increase its capacity and use of the available potential. This article deals with the financial capacity of Slovak cities, which reflects their ability to ensure their development. The financial capacity of Slovak cities was investigated in time period 2009 – 2014. Investigated were all 138 Slovak cities and they were divided into three size groups: small cities with population up to 20 000 inhabitants, medium-sized cities with population between 20 001 and 50 000 inhabitants and large cities over 50 001 inhabitants. The evaluation of financial capacity was realized on six indicators: current account balance, capital account balance, total debt, debt service, immediate liquidity and net worth. The comparison of the calculated values of each group showed that the highest amount of resources allocate to their development the group of largest cities. On the other hand, that group has also the highest debt.
Keywords: development of cities; financial capacity; current account; capital account; total debt; G32; H63; R51